The Anti-poverty Effectiveness of Child Maintenance: A Comparative Study - Reja, Shimul (My University, 2023)
This study explores the anti-poverty effectiveness by using comparative analysis on child maintenance in single-parent families in Estonia, Greece, Italy, and Lithuania. Additionally, the study examines the child poverty rates in two-parent and single-parent families in these countries. The current study utilized the Luxembourg Income Study (LIS) data wave X in 2016, with 16,099 observations. The study aims to answer two questions: 1) Are children in two-parent families better off than children in single-parent families? 2) Do child maintenance transfers effectively reduce child poverty in single-parent families? This study found that child maintenance transfers reduce child poverty and lifted 7% to almost 43% of children out of poverty for those single-parent families receiving child maintenance in studied countries. However, the effect varies across countries because countries have different child maintenance schemes and systems, and only some eligible single parents receive child maintenance. Furthermore, child maintenance transfers also reduce poverty gaps. The study also reveals that children in two-parent families are generally better off than children in single-parent families, highlighting the economic insecurity of single-parent families in these countries.
Keywords: Child maintenance, anti-poverty effectiveness, child maintenance schemes, and family structure